The Problem of Development and Enrichment of the Vocabulary of the English Language of Philosophy in XYI Century - Hakimova Mukhabbat Alimovna (International Journal on Orange Technologies, 2021)
The article is devoted to the coverage of issues related to the initial period of the formation and development of the lexicon of English philosophy of the Renaissance period (XY-XYI centuries). The author gives his own interpretation of this issue, based on numerous examples from the original works on the history of English philosophy.